2020
DOI: 10.15302/j-fase-2019304
|View full text |Cite
|
Sign up to set email alerts
|

Livestock breeding for the 21st century: the promise of the editing revolution

Abstract: In recent years there has been a veritable explosion in the use of genome editors to create sitespecific changes, both in vitro and in vivo, to the genomes of a multitude of species for both basic research and biotechnology. Livestock, which form a vital component of most societies, are no exception. While selective breeding has been hugely successful at enhancing some production traits, the rate of progress is often slow and is limited to variants that exist within the breeding population. Genome editing prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The recent discovery of gene editing, a controlled change in the DNA of a living organism, opens the possibility of solving issues related to animal production [12]. Gene editing proponents promise solutions for animal health and welfare problems facing the livestock industries [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of gene editing, a controlled change in the DNA of a living organism, opens the possibility of solving issues related to animal production [12]. Gene editing proponents promise solutions for animal health and welfare problems facing the livestock industries [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…AFB 1 can also negatively impact meat quality due to associated oxidative stress, inflammation, and the dysregulation of gut microbiota and dysbiosis in animals [ 11 , 12 ]. Various physical, chemical, and biological approaches to preventing AFB 1 contamination have been developed [ 13 , 14 , 15 ]. For instance, transgenic pigs expressing aflatoxin-detoxifizyme (ADTZ) exhibit resistance to AFB 1 toxicity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene editing is a further development in breeding that facilities faster genetic advancement than the more traditional genetic selection techniques. Gene editing is proposed as a means to improve animal health, animal welfare, and production efficiency and to create the potential to produce milk with reduced allergenic potential, through the controlled manipulation of DNA in a single generation [32,65]. In research on Brazilian consumers, it was identified that the acceptability of gene editing in cattle was increased by perceptions of benefits to animals, and influenced by the perceived distribution of benefits [32].…”
Section: Breedingmentioning
confidence: 99%